Alternative lengthening of telomeres does exist in various canine sarcomas. Issue 3 (22nd September 2016) - Kreilmeier, Theresa; Sampl, Sandra; Deloria, Abigail J.; Walter, Ingrid; Reifinger, Martin; Hauck, Marlene; Borst, Luke B.; Holzmann, Klaus; Kleiter, Miriam
Abstract : Alternative lengthening of telomeres (ALT) is a telomere maintenance mechanism (TMM) found in some human tumors such as sarcomas. Canine tumors are not characterized for ALT and the study aim was to identify if the ALT phenotype exists in canine sarcomas. Sixty‐four canine sarcoma samples (20 snap‐frozen, 44 FFPE) as well as six canine sarcoma cell lines were screened for ALT by C‐circle assay. ALT was further evaluated by measuring telomere length via qPCR and telomere restriction‐fragments including pulsed‐field electrophoresis. ALT‐associated proteins were validated by immunohistochemistry. Further, telomerase activity (TA) and gene expression were analyzed by TRAP and qPCR. DNA from 20 human neuroblastomas and 8 sarcoma cell lines served as comparative controls. ALT was detected in 9.4% (6/64) canine sarcomas including aggressive subtypes as hemangiosarcoma, osteosarcoma, and histiocytic sarcoma. C‐circle levels were comparable with human ALT‐positive controls. All ALT tumors demonstrated loss of ATRX expression and 5/6 showed strong p53 expression. TA was detected in 93% (14/15) snap‐frozen samples including a sarcoma with ALT activity. This tumor showed long heterogeneous telomeres, and a high level of colocalization of DAXX with telomeres. One sarcoma was ALT and TA negative. All canine and human sarcoma cell lines were ALT negative. In this study, we demonstrated that canine sarcomas use ALT. As in humans, ALT was identified in aggressive sarcomas subtypes and coexisted with TA in one tumor. Overall, canine sarcomas seem to share many similarities with their human counterparts and appear an attractive model for comparative telomere research. © 2016 Wiley Periodicals, Inc.